Nurses’ Work Motivation Based on Maslow’s Hierarchy of Needs in the Inpatient Wards of a Psychiatric Hospital: A Descriptive Cross-Sectional Study - Mundakir Mundakir; Dwi Nurcahyono; Siswanto Agung Siswanto Agung; Reliani Reliani; Diah Priyantini (Indonesian Academia Health Sciences Journal, 2026)
Background: Nurses working in psychiatric inpatient settings provide continuous care in environments characterized by complex patient needs, safety concerns, emotional demands, and shift-based work. Work motivation is therefore important for sustaining nursing performance and service quality. Maslow’s hierarchy of needs offers a multidimensional framework for examining whether nurses’ physiological, safety, affiliation, esteem, and self-actualization needs are being met. Objective: To describe nurses’ work motivation according to the five domains of Maslow’s hierarchy of needs in the inpatient wards of a psychiatric hospital in Surabaya, Indonesia. Methods: This descriptive cross-sectional study included 79 inpatient staff nurses selected from a population of 98 nurses using purposive sampling. Eligible participants were civil-service or public-service-agency staff nurses, had worked for more than one year, and held a diploma or professional nursing qualification. Data were collected using a Likert-type questionnaire adapted from a previous work-motivation instrument. Domain scores were classified as good (76%–100%), moderate (56%–75%), or poor (<56%). Data were summarized using frequencies and percentages. Results: The sample was almost evenly divided by sex (50.6% women), and 40.5% were aged 41–50 years. Most nurses held a diploma in nursing (81.0%), and 39.2% had worked for more than 10 years. The proportion classified as having good motivation was 62.0% for physiological needs, 64.6% for safety and security needs, 87.3% for affiliation and acceptance needs, 91.1% for esteem and status needs, and 68.4% for self-actualization needs. Esteem and status represented the strongest domain, whereas physiological needs had the lowest proportion in the good category. Conclusion: Most inpatient psychiatric nurses reported good motivation across all five Maslow domains, particularly in esteem and affiliation. Nevertheless, approximately one-third of nurses did not reach the good category for physiological, safety, or self-actualization needs. Hospital managers should maintain recognition and supportive relationships while strengthening compensation adequacy, workplace safety, career development, and opportunities for professional growth.